Report on industrial attachment with Air Logistics Department, RSAF Aerosystems Branch - Chua, Chern Yi. (2008)
The objective of the attachment was for the author to perform the role of Operations and Support (O&S) Engineer like the engineers in the Branch and attend to practical engineering problems on the basis of day-to-day work.